THU0564 Validation of the Dutch-Flemish PROMIS Physical Functioning Item Bank in Patients with Chronic Pain. (10th June 2014) - Crins, M.H.; Terwee, C.B.; Smits, N.; de Vries, A.; de Vet, H.C.; Dekker, J.; Westhovens, R.; Cella, D.; Cook, K.F.; Revicki, D.; van Leeuwen, J.; Boers, M.; et al.
Abstract : Background: In the assessment of chronic pain patients it is important to measure physical functioning. The National Institutes of Health's Patient-Reported Outcomes Measurement Information System (PROMIS) initiative developed an item bank for measuring physical functioning. This PROMIS physical functioning item bank was translated into Dutch-Flemish language according to the FACIT methodology 1 . Objectives: The aim of current study was to validate the Dutch-Flemish translation of the PROMIS physical functioning item bank (DF-PROMIS-PF) in patients with chronic pain. Methods: A paper-and-pencil or web-based survey including the full DF-PROMIS-PF (124 items), was completed by 857 chronic pain patients (77% female, mean age 49y) referred to an outpatient secondary care center for rheumatology and rehabilitation in the Netherlands. One-dimensionality was evaluated by one-factor confirmatory factor analysis. With the future strategy to develop computer adaptive tests (CAT), item response theory (IRT) models were used to evaluate the item characteristics of the two item banks. A graded item response model (GRM) was fitted and Differential Item Functioning (DIF) was evaluated for e.g. language (Dutch vs. English), by ordinal regression models. Furthermore, construct validity was studied. Results: Through computer technical limitation, the item bank was separated during statistical analysis into DF-PROMIS-PFA (51 PFA-items) and DF-PROMIS-PFBC (45 PFB - and 28 PFC -items). These interim analysis showed that the DF-PROMIS-PFA and DF-PROMIS-PFBC demonstrated good fit to a one-dimensional model (both CFI=0.976 and TLI=0.975). The first factor accounted for 57% of the questionnaire variance. The results showed acceptable testinformation (SE<0.3) for theta between -2.3 and 3.8 for DF-PROMIS-PFA and between -1.6 and 4 for DF-PROMIS-PFBC . 103 out of 1275 (8%) DF-PROMIS-PFA item pairs and 130 out of 1431 (9%) DF-PROMIS-PFBC item pairs were marked as possibly locally dependent. The items demonstrated no DIF with respect to survey version. DIF was present with respect to gender (2 items), age (4 items) and language (11 items). However, the impact of DIF on the total item scores was minimal. Conclusions: The first results indicate that the DF-PROMIS-PF fits a GRM and demonstrates good coverage across the range of the physical functioning domain. Nearly all Dutch item parameters match the American item parameters and likely Dutch-specific item calibrations are not needed. The DF-PROMIS-PF can be used to develop a CAT. References: Terwee CB, Roorda LD, de Vet HCW, Dekker J, Westhovens R, van Leeuwen J, Cella D, Correia H, Arnold B, Perez B, Boers M. Dutch-Flemish translation of 17 item banks from the Patient Reported Outcomes Measurement Information System (PROMIS). Quality of Life Research in press. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1721